2019
DOI: 10.3233/jad-190567
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes as Biomarkers for Dementia: Analysis of Protein Content and Alpha-Synuclein

Abstract: Background: Discovering biomarkers for dementia is a pivotal step toward successful early diagnosis and treatment. Although plasma biomarkers have been explored, no consensus has been reached. Alpha-synuclein (AS), a 14 kDa synaptic protein associated with several neurodegenerative diseases, exists natively within erythrocytes (ERC). This protein is characteristic of Lewy body diseases, in which it aggregates into toxic Lewy bodies. As ERC are implicated in dementia, they are a potential target for future biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Homogenates of tissue were prepared essentially as described previously for the multiplex cytokine assays (14). Fibrinogen was determined using a sandwich ELISA (25). PDGFR‐β was assayed as specified by the manufacturer (Human Total PDGFR beta DuoSet IC ELISA, DYC385, R&D Systems, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…Homogenates of tissue were prepared essentially as described previously for the multiplex cytokine assays (14). Fibrinogen was determined using a sandwich ELISA (25). PDGFR‐β was assayed as specified by the manufacturer (Human Total PDGFR beta DuoSet IC ELISA, DYC385, R&D Systems, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in the last two decades probed the amount of α-syn in the blood, CSF and other fluids including saliva as a feasible marker in PD (Vivacqua et al 2016 ; Wang et al 2015 ). These studies became more and more elaborated in detecting specific protein conformation and providing a significant correlation between PD and specific isoform of α-syn in various fluids (Majbour et al 2021 ; Wang et al 2015 ; Graham et al 2019 ). Again, since α-syn accumulation is related to an impairment of its metabolism which mainly takes place via the autophagy machinery (Petroi et al 2012 ; Limanaqi et al 2020 ; Langston and Cookson 2020 ), autophagy-related proteins were measured in PD patients (e.g., Wu et al 2011 ; Miki et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effective components of erythrocytes in the central nervous system are not limited to Hb. The aforementioned cholinesterase activity, amyloid-β and α-synuclein are closely related to cognitive impairment (von Bernhardi et al, 2005;Lauriola et al, 2018;Graham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes contain a large number of important biologically active media (such as cholinesterase activity, amyloid-β, αsynuclein, hydroxyoctadecadienoic acid, oxidatively modified peroxiredoxin, magnesium, catalase activity, and superoxide dismutase), which play important roles in the central nervous system through circulatory functions of their carrier (von Bernhardi et al, 2005;Yoshida et al, 2009;Lauriola et al, 2018;Graham et al, 2019;Sitzia et al, 2020). With the chronic effects of vascular risk factors or stroke events, the imbalance in these components in erythrocytes or alterations in membrane surface receptors are not only closely related to cognitive impairment but also are important potential predictors of the occurrence and development of VCI (von Bernhardi et al, 2005;Yoshida et al, 2009;Lauriola et al, 2018;Graham et al, 2019;Sitzia et al, 2020). Studies have found that in elderly patients, severe chronic anemia can increase white matter stroke by 1.8 times, which is an independent risk factor for stroke exacerbation and cognitive impairment (Inzitari et al, 2008;Hao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%